2011
DOI: 10.1136/bjophthalmol-2011-300487
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of the TED-QOL: a new three-item questionnaire to assess quality of life in thyroid eye disease

Abstract: The TED-QOL is rapid and easy to complete and analyse and has similar validity and reliability to longer questionnaires. All questionnaires showed only moderate correlation with disease severity, emphasising the discrepancy between objective and subjective assessments and the importance of measuring both.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 10 publications
0
44
0
3
Order By: Relevance
“…Although this multivector strabismus can be corrected with a single surgical plan, more than one correction may be required to reach the desired outcome (Eckstein et al 2012;Jellema et al 2012)an adequate field of binocular single vision (BSV) in primary and downgaze. At this time, a few disease-specific questionnaires for GO are available which have been tested under different circumstances (Terwee et al 2002;Yeatts 2005;Fayers & Dolman 2011). At this time, a few disease-specific questionnaires for GO are available which have been tested under different circumstances (Terwee et al 2002;Yeatts 2005;Fayers & Dolman 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this multivector strabismus can be corrected with a single surgical plan, more than one correction may be required to reach the desired outcome (Eckstein et al 2012;Jellema et al 2012)an adequate field of binocular single vision (BSV) in primary and downgaze. At this time, a few disease-specific questionnaires for GO are available which have been tested under different circumstances (Terwee et al 2002;Yeatts 2005;Fayers & Dolman 2011). At this time, a few disease-specific questionnaires for GO are available which have been tested under different circumstances (Terwee et al 2002;Yeatts 2005;Fayers & Dolman 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The field of BSV and the quality of life (QoL) are among recently published criteria defining successful treatment (Jellema et al 2015), in which the patient reported outcome is complementary to the clinically measured outcome (Sprangers 2010). At this time, a few disease-specific questionnaires for GO are available which have been tested under different circumstances (Terwee et al 2002;Yeatts 2005;Fayers & Dolman 2011). The GO-QoL is used in a pilot study evaluating the impact of a first strabismus surgery (Jellema et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Entre los factores que contribuyen a este deterioro están: alteraciones en la función visual, discomfort ocular y alteraciones en la apariencia física, los que producen una peor autoimagen, problemas de sueño y mal rendimiento social y laboral 43 . Existe un instrumento de evaluación de calidad de vida enfermedad específico validado, llamado GO-QoL 44 , herramienta que puede ser usada para medición de outcomes primarios en ensayos clínicos.…”
Section: Imágenesunclassified
“…Specific quality of life questionnaires have been developed to assess the impact of these phenomena in patients with GO (Terwee et al. ; Fayers & Dolman ).…”
Section: Introductionmentioning
confidence: 99%
“…It limits the affected patient seriously in many daily life activities such as car driving, walking or reading (Gerding et al 1997;Terwee 2000;Farid et al 2005;Yeatts 2005;Bradley et al 2006;Coulter et al 2007). Specific quality of life questionnaires have been developed to assess the impact of these phenomena in patients with GO (Terwee et al 1998;Fayers & Dolman 2011).…”
Section: Introductionmentioning
confidence: 99%